The ultimate isometric path number of a graph - Clarke, Nancy E. (Utilitas Mathematica, 2008)
The isometric path number of a graph G is the minimum number of isometric paths needed to cover the vertices of G. We provide bounds on the isometric path numbers of powers of graphs under a variety of products. In many cases, the results are shown to be asymptotically exact.